THE EFFECTIVENESS OF LAVENDER AND ROSE AROMA THERAPY ON THE LEVEL OF MOTHER'S ANXIETY IN FACING SC LABOR - Syaiful, Yuanita; Fatmawati, Lilis; Aisy, Rohadatul (jfpublisher, 2024)
Introduction : According to Mochtar (2011) Section Caesarea is a method of giving birth to a fetus by making an incision in the uterine wall through the front of the abdomen or vagina or also called hysterotomy to give birth to a fetus from inside the uterus. Adaptive response Positive results will be obtained if the individual can accept and manage anxiety. This study aims to determine the effectiveness of lavender and rose aroma therapy on the level of anxiety in mothers in dealing with cesarean delivery at the hospital. Surya Medika. Method : The research design used in this study was Quasy Experimental with a pre-post test design. The sample was selected using purposive sampling method. Samples were taken as many as 40 respondents. Divided into 2 groups of 20 respondents in the intervention by giving lavender aroma therapy and 20 respondents in the intervention by giving rose aroma therapy. The independent variables were lavender and rose scented terpai. The dependent variable is the expenditure of t. Data collection on the level of maternal anxiety. SOP (Standard Operating Procedure) Lavender Aroma Therapy, SOP (Standard Operating Procedure) Rose Aroma Therapy and questionnaire sheet. Wilcoxon test results obtained p value = 0.000 for lavender and rose aroma therapy where <0.05 which means that there is an effect on breast milk production. Result & Analysis : The results of the Mann Whitney U Test statistical test showed an insignificant value of p = 0.426 where > 0.05 which means H1 was rejected, so there was no significant difference between giving lavender aroma therapy and rose aroma therapy to anxiety levels. Discussion : Giving lavender aroma therapy and giving rose aroma therapy can be used to reduce SC anxiety levels. Lavender aroma therapy was more effective on the mother's golden level in dealing with cesarean delivery, compared to rose aroma therapy